IMPLEMENTASI KEBIJAKAN PENANGANAN ORANG DENGAN GANGGUAN JIWA (ODGJ) DI RUMAH SAKIT JIWA ABEPURA - Hamadi, yonece; Aedah, Nur; Poli, Agustina Ivonne (JURNAL KEBIJAKAN PUBLIK, 2025)
This study aims to analyze the implementation of policies for handling People with Mental Disorders (ODGJ) at Abepura Mental Hospital. The background of this research focuses on the importance of fulfilling human rights for ODGJ, which is regulated in the Law of the Republic of Indonesia. The theoretical study uses George C. Edwards III's policy implementation model, which includes four key variables: communication, resources, executive disposition, and bureaucratic structure. The research method used was qualitative with a phenomenological approach, involving in-depth interviews with key informants from the Social Service, Abepura Hospital, and ODGJ families. The results of the study show that communication between agencies is going well, but human resources and facilities are still limited, hindering optimal service. The attitude of the implementers shows a positive attitude and high commitment in handling ODGJ, despite the challenges in the bureaucratic structure that are not yet fully supportive. The conclusion of this study confirms that the implementation of the policy for handling ODGJ at Abepura Hospital has been running well, but still needs improvement in terms of resources and facilities. The suggestions given include increasing the number of mental health workers, strengthening facilities and infrastructure, and educating the public to reduce stigma against ODGJ. This research is expected to provide recommendations for related parties in improving mental health services in Papua.